Effect of paddy straw incorporation and nitrogen levels on oil yield, seed yield and B: C ratio of mustard (Brassica juncea L.): Effect of paddy straw incorporation and nitrogen levels on oil yield, seed yield and B: C ratio of mustard (Brassica juncea L.) - V MOUNIKA; K CHANDRASHAKER; A KRISHNA CHAITANYA; G SATYANARYANA REDDY (Journal of Oilseeds Research, 2023)
Incorporation of paddy straw along with of 20% excess nitrogen (T6) over recommended dose (60:40:40) to mustard significantly increased the seed and oil yield and higher B: C ratio compared to residue burning (T1) and residue removal (T2) treatments.